The Effect of Tabah Bamboo Liquid Smoke (Gigantochloa Nigrociliata Buse-Kurz) Concentration and Ovening Temperature of White Pomfret (Pampus Argenteus) - Simbolon, Nova Syafrienti; Kencana, Pande Ketut Diah; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
White pomfret (Pampus argenteus) is a fish that has high nutrition and is easily damaged. A way to preserve white pomfret is used inthe smoking process. The purpose of this study was to measure and obtain the concentration of liquid smoke of tough bamboo and the appropriate oven temperature in order to obtain the best quality of white pomfret. This study used a two-factorial Completely Randomized Design. The first factor is the concentration of liquid smoke which consists of concentrations of 0%, 3%, and 6%. The second factor is the oven temperature of white pomfret with temperatures of 60°C, 80°C, and 100°C for 4 hours. The best treatment combination was at a concentration of 6% and an oven temperature of 100°C to produce white pomfret with the following characteristics: water content 26.37%; protein content 8.23%; pH 5.99; fat 9.62%; the value of the sensory appearance test is 8.20; fragrance 8.20; flavor 8.20; and texture 9.00.